Pengelolaan Badan Usaha Milik Desa melalui Pendekatan Collaborative Governance - Rendi Priono; Rafly Ramadan; Juliardi Dwi Anggoro (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2025)
The aim of this study was to determine the management of village-owned enterprises through a collaborative governance approach at the village-owned enterprises of Wasuni Mainawa, the village of Suka Maju, the village of Wolowa, the regency of Buton. Qualitative methods can be used to reveal and understand something behind a phenomenon that is not even minimally known.The results of the study show: 1) The face-to-face dialogue has been carried out more than once, which has the character of formal and non-formal. Each phase of the development of BUMDesa is inseparable from the presence of face-to-face dialogue that can improve communication by facilitating the cultivation of trust, the conduct of negotiations and the achievement of the desired results. 2) The building of trust is formed when a face-to-face dialogue takes place, that is, by building a good image, understanding information, potential, opportunities and seriousness in carrying out the collaboration. 3) Process engagement is carried out during face-to-face dialogue inspiring stakeholder engagement, providing motivation and mutual understanding. 4) Sharing Understanding (Sharing Understanding) collaboratively in developing BUMDes was done well with understanding common goals. 5) The interim results of the BUMDesa development program were found to be able to meet the needs of the community